Predictors of financial security among female-headed households in Malaysia - Ahmad, Siti Yuliandi (2016)
Financial security is linked to the level of savings, the ability of individuals to meet an emergency, the adequacy of financial resources in retirement and the availability of income. The main objective of this study was to examine predictors of financial security among female-headed households in Malaysia. The predictor of financial security consisted of financial strains, financial literacy and financial practices. The backbone theory used was Life-cycle Theory and the supportive theory of Cognitive of Stress and Coping Theory and Characteristics Theory as the basis for the theoretical framework. A conceptual framework was developed from the theoretical setting to examine the association between financial strains, financial literacy, financial practices and self-coping mechanisms on financial security. The main contributions of this study were to examine the mediating effect of self-coping mechanisms and the moderating effect of work status in the relationships between financial strains, financial literacy, financial practices and financial security. The moderating effect of work status was examined by ascertain working and not working group that influences financial security of female-headed households. A multistage random sampling was used to gather the data of 600 female-headed households from six single mother associations registered under the Ministry of Women, Family and Community Development in Malaysia. The selfadministered questionnaires were distributed by the President from each identified single mother association to their members. There were 521 usable responses for the analysis of the study. The data were statistically analysed using descriptive analysis of Pearson Product Moment Correlation and Structural Equation Modelling. There were positive significant relationships found between financial strains, self-coping mechanisms, financial literacy, financial practices and financial security. The structural equation of financial security model showed a relatively good fit to the data obtained in the study. The self-coping mechanisms were distinguished as a mediator in the relationships between financial strains, financial literacy, financial practices and financial security. The self-coping mechanisms illustrated an increase of 45% to the direct model (41%) in explaining the variance in the financial security model. In testing the mediation effect, the indirect mediation existed in the relationships between financial strains and financial literacy toward financial security. Meanwhile the partial mediation existed in the relationship between financial practices and financial security. Moderation effect of work status was demonstrated and although not working and working models did not share the same regression weight, however the predictors of financial security were similar for the two groups. This study seems to support the importance of behavioural finance in line with notable empirical findings and the theoretical reasoning in understanding financial security of female-headed households. The implications and recommendations have been highlighted in this study, such as social support programme and financial education programme for female-headed households in Malaysia. This study also highlights a future research necessity for financial security.